2014
DOI: 10.1208/s12248-014-9649-9
|View full text |Cite
|
Sign up to set email alerts
|

The Poorly Membrane Permeable Antipsychotic Drugs Amisulpride and Sulpiride Are Substrates of the Organic Cation Transporters from the SLC22 Family

Abstract: Abstract. Variations in influx transport at the blood-brain barrier might affect the concentration of psychotropic drugs at their site of action and as a consequence might alter therapy response. Furthermore, influx transporters in organs such as the gut, liver and kidney may influence absorption, distribution, and elimination. Here, we analyzed 30 commonly used psychotropic drugs using a parallel artificial membrane permeability assay. Amisulpride and sulpiride showed the lowest membrane permeability (P e <1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 52 publications
3
53
0
1
Order By: Relevance
“…Whether these differences are explained by the extreme age of participants in the current study, their diagnosis, or possibly both, is unclear, but there is certainly evidence that BBB integrity is disrupted (increased permeability and reduced expression of efflux transporters) with age and more profoundly affected by Alzheimer's disease (Zeevi et al, 2010). A further consideration is our choice of amisulpride, which has low lipophilicity, shows poor BBB penetration relative to other antipsychotics (Natesan et al, 2008) and has been identified as a substrate for several BBB transporters, including the efflux transporter pglycoprotein (Schmitt et al, 2012), and the widely expressed (brain, biliary, renal) organic cation transport system (Dos Santos Pereira et al, 2014, Sekhar G, 2016. These properties may mean that amisulpride is a more sensitive tool with which to explore BBB disruption than antipsychotics previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these differences are explained by the extreme age of participants in the current study, their diagnosis, or possibly both, is unclear, but there is certainly evidence that BBB integrity is disrupted (increased permeability and reduced expression of efflux transporters) with age and more profoundly affected by Alzheimer's disease (Zeevi et al, 2010). A further consideration is our choice of amisulpride, which has low lipophilicity, shows poor BBB penetration relative to other antipsychotics (Natesan et al, 2008) and has been identified as a substrate for several BBB transporters, including the efflux transporter pglycoprotein (Schmitt et al, 2012), and the widely expressed (brain, biliary, renal) organic cation transport system (Dos Santos Pereira et al, 2014, Sekhar G, 2016. These properties may mean that amisulpride is a more sensitive tool with which to explore BBB disruption than antipsychotics previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…OCT1 and other transporters are highly genetic polymorphic. Compared to the wild‐type OCT1*1 variant, the uptake of drugs was significantly lower in cells expressing the loss‐of‐function OCT1 variants OCT1*2 to *6 . Low‐activity genotypes of OCT1 and OCTN2 were related to a decrease in the renal clearance rate.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to the influence of dose on concentration, many other factors have been associated with increased concentration. Amisulpride is a substrate of SLC22 transporters (organic cation transporter 1 [OCT1], OCT2, OCT3, OCTN1, OCTN2) expressed in organs such as the intestine and kidney, which may influence absorption, distribution and elimination . OCT1 and other transporters are highly genetic polymorphic.…”
Section: Discussionmentioning
confidence: 99%
“…Only AMI, which is poorly membrane permeable, reaches lower concentrations in the brain. However, it is a substrate of organic cation transporters, which may play an important role in its distribution to the brain [22] . These transporters were found to be expressed in U-87MG cells at both mRNA and protein levels, which may allow AMI to enter U-87MG cells [23] .…”
Section: Discussionmentioning
confidence: 99%